Mid-Infrared Frequency Generation via Intermodal Difference Frequency Generation in AlGaAs-On-Insulator Waveguides - Haines, Jack; Gandolfi, Marco; Franz, Yohann; De Angelis, Costantino; Guasoni, Massimiliano (Frontiers in Photonics, 2021)
We investigate theoretically mid-infrared (MIR) generation via difference frequency generation in multimode AlGaAs-on insulator (AlGaAs-OI) waveguides. The large refractive index difference between the AlGaAs core and the silica cladding shrinks the modes size down to the sub-µm scale, and, together with AlGaAs strong second order nonlinear polarization, empowers strong nonlinear effects. As a result, efficient MIR generation is obtained in few-cm long waveguides with sub-µm transverse section, where higher order modes are exploited to achieve the phase matching condition. These observations suggest that multimode AlGaAs-OI waveguides could represent a novel promising platform for on-chip, compact MIR sources.